Design and implementation of embedded vision-based tracking system using FPGA-SoC / \c Saif Najim Ismail. - Ismail, Saif Najim (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The objectives of this project are ; to design and implement a passive embedded based vision tracking system using FPGA-SoC with the following features ; multiple objects concurrently ; multiple color detection ; to verify and improve images and video processing speed forbetter and faster throughput based on CAD tool and on FPGA board.